Analisis Keputusan Pembelian Produk Ramah Lingkungan Vegan Leather Basis Limbah Kopi (Studi Kasus pada PT KLK) - Fathiyyah, Nizzah Nailul; Purnomo , Dwi; Noerwardhani , Rr. Gita (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
PT KLK is a small and medium-scale enterprise (SMEs) in Bandung focused on utilizing coffee waste to create eco-friendly products. One of its leading innovations is vegan leather made from coffee husk waste, which is used as a growth medium for mycelium to produce sustainable alternative leather sheets. This innovation was designed to address two primary issues: coffee processing waste and the negative impact of the fast fashion industry. However, PT KLK is not yet the primary choice in consumers' minds as a substitute for animal or synthetic leather. This study aims to understand the factors influencing purchasing decisions based on customer insights, to develop products that are more aligned with users' needs and expectations. A mixed-methods approach was used in this study, involving the Henry Garrett Ranking method within the Sustainable Consumption Behavior (SCB) framework, involving 6 experts and 58 potential users, and in-depth interviews with 42 respondents with five levels of green lifestyle maturity. The results indicate that the five main criteria in purchasing decisions are: price (67.01), environmental impact (65.93), product specifications (61.15), sustainability value (56.84), and product information (56.53). Through the SCB framework, it was found that price remains the primary factor due to the limited support from environmental, personal, cultural, and economic motivations that would encourage consumers to choose environmentally friendly products. However, consumers are still willing to consider other aspects, such as user experience and support for sustainable lifestyles, when a supportive ecosystem is available. Therefore, this study proposes three promotional strategies—a “DIY Your Own Wallet” workshop, the “KOPI BERI INDONESIA” community, and an interactive “Feel the Future” exhibition—to increase consumer engagement and strengthen the product’s market position.